Analisis Penerapan Pendidikan Pancasila Dalam Kerangka Kurikulum Merdeka Di SMA Negeri 17 Surabaya - Isyanto; Suhartono (Jurnal Kajian dan Penelitian Umum, 2025)
Pancasila as the basis of the state and the nation's outlook on life faces great challenges in maintaining its relevance in the era of globalization. The education system, especially through the Independent Curriculum, is a strategic instrument to internalize the values of Pancasila in the younger generation. This research aims to analyze the implementation of Pancasila education at SMA Negeri 17 Surabaya, including its opportunities, challenges, and innovations. A qualitative approach with a descriptive design was used, with data obtained through observation, interviews, and document analysis, and analyzed using the Miles and Huberman model. The results of the study show that Pancasila education is integrated through project-based learning methods, discussions, and case simulations. This activity increases student engagement, despite barriers such as a lack of teacher training and teaching modules that are not fully applicable. School principals support Pancasila values-based policies, but parental involvement needs to be increased. The conclusion shows that the implementation of the Independent Curriculum opens opportunities for more applicable Pancasila education, but challenges such as teacher competence and limited resources need to be overcome. It is recommended that there be intensive training, the development of contextual modules, and strengthening collaboration between teachers, students, and parents. This research contributes to the development of relevant and sustainable Pancasila education.